2019
DOI: 10.1002/eqe.3165
|View full text |Cite
|
Sign up to set email alerts
|

Analytical solution of seismic response of base‐isolated structure with supplemental inerter

Abstract: Summary Closed‐form solutions are derived for the modal characteristics and seismic response of a base‐isolated structure equipped with additional inerters. By simplifying the structure‐isolator‐inerter system in terms of the two‐degree‐of‐freedom (2DOF) model, the modal frequencies, mode shapes, damping ratios, and participation factors of the system are derived. Consequently, analytical seismic response solutions are formulated by the modal superposition method. Utilizing these analytical solutions, an exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…1,2 Many studies have been conducted to propose various device and structural control approaches in order to reduce the vibration response produced by earthquakes, wind, etc. [3][4][5][6][7] As a recently introduced mechanical element for structural control, the inerter has attracted an increasing amount of attention and has been studied in different fields, from the improved suspension system in mechanical [8][9][10][11][12] and railway engineering 13,14 to the protection of building structures, [15][16][17][18][19][20][21][22][23][24][25] storage tanks, [26][27][28] wind turbine towers, 29,30 platforms, 31 and performanceimproved cables [32][33][34][35] and isolation systems [36][37][38][39][40][41][42][43][44][45] in civil engineering. An inerter is a type of two-terminal inertia element, and its relative motion can be produced between the two termi...…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Many studies have been conducted to propose various device and structural control approaches in order to reduce the vibration response produced by earthquakes, wind, etc. [3][4][5][6][7] As a recently introduced mechanical element for structural control, the inerter has attracted an increasing amount of attention and has been studied in different fields, from the improved suspension system in mechanical [8][9][10][11][12] and railway engineering 13,14 to the protection of building structures, [15][16][17][18][19][20][21][22][23][24][25] storage tanks, [26][27][28] wind turbine towers, 29,30 platforms, 31 and performanceimproved cables [32][33][34][35] and isolation systems [36][37][38][39][40][41][42][43][44][45] in civil engineering. An inerter is a type of two-terminal inertia element, and its relative motion can be produced between the two termi...…”
Section: Introductionmentioning
confidence: 99%
“…Later, studies on clutching inerter damper (CID) for seismic response control of structures were conducted, and they were found to be quite effective 10–13 . The use of inertial devices to improve the performance of a base‐isolated structure was also reported 14–17 . The performance of base‐isolated structures with supplemental tuned mass damper inerter (TMDI) has recently been investigated, and it has been found that the TMDI is effective in mitigating the seismic response 18–21 .…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] The use of inertial devices to improve the performance of a base-isolated structure was also reported. [14][15][16][17] The performance of base-isolated structures with supplemental tuned mass damper inerter (TMDI) has recently been investigated, and it has been found that the TMDI is effective in mitigating the seismic response. [18][19][20][21] De Angelis et al 22 assessed the optimal tuning of the TMDI for base-isolated structures and confirmed the effectiveness of TMDI for seismic vibration control.…”
Section: Introductionmentioning
confidence: 99%
“…These systems involve general structural systems including discrete structure system [24,25,[27][28][29][30][31] and distributed-parameter system, [32][33][34] TMD system, [26,35] and base isolation system (BIS) system. [36,37] These inerter-based devices have proved to be effective in improving the performance of the systems considered. However, in many cases, the performance of the inerter seems limited.…”
Section: Introductionmentioning
confidence: 99%